The Effect Of Growth Hacking, Brand Image, Electronic Word Of Mouth On Repurchase Decisions On Beauty Products (Study On Adara Cosmetics) - Nafiria Zephaniah Abraham; Lamhot Henry Pasaribu (Enrichment : Journal of Management, 2022)
Market competition in the field of beauty products is getting tougher, causing many manufacturers to issue strategic marketing steps to introduce their products to the public. Manufacturers must have creative ways to appear superior to their competitors. Especially in today's digital era which increases opportunities for online customers to get access more easily to products or services of interest at competitive prices. Growth hacking, brand image, and electronic word of mouth are thought to effect repurchase intention. This research method uses inferential research type. The research sample used purposive random sampling technique. The data source uses primary data by distributing questionnaires. The analysis technique used is SEM-PLS and using a computer program. The results of the study showed that: (1) Growth Hacking has a positive and significant effect on Repurchase Intention; (2) Brand Image has a positive and significant effect on Repurchase Intention; (3) Electronic word of mouth has a positive and significant effect on repurchase intention